2015
DOI: 10.1155/2015/191075
|View full text |Cite
|
Sign up to set email alerts
|

Tyre Volume and Pressure Effects on Impact Attenuation during Mountain Bike Riding

Abstract: Exposure to impacts and vibrations has been shown to be detrimental to cross country mountain bike performance and health. Therefore, any strategy aimed at attenuating such exposure is useful to participants and/or industry. The purpose of this study was to assess the influence of tyre size and tyre inflation pressure on exposure to impacts. Participants completed nine trials of a technical section (controlled for initial speed and route taken) including nine separate conditions involving three tyre sizes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…Overall, it appears than employing strategies to mitigate vibration exposure during enduro mountain biking will benefit performance. Previous studies have shown different components, frames and tyre pressure to have different vibration transmission properties (Lépine et al 2015;Macdermid et al 2015). Therefore, further work is required to explore the vibration transmission of different components with the aim to find means to reduce vibration exposure in mountain biking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, it appears than employing strategies to mitigate vibration exposure during enduro mountain biking will benefit performance. Previous studies have shown different components, frames and tyre pressure to have different vibration transmission properties (Lépine et al 2015;Macdermid et al 2015). Therefore, further work is required to explore the vibration transmission of different components with the aim to find means to reduce vibration exposure in mountain biking.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the broad range of research concerning road or commuter cycling, to the authors' knowledge, there has been no attention given to the hand-arm and handtransmitted vibration that mountain bike enduro athletes are exposed to. Additionally, studies that have explored magnitude of vibration experienced by downhill (Hurst et al 2013) and cross-country riders (Macdermid et al 2014(Macdermid et al , 2015 were limited by the fact that they did not meet the analysis requirements of hand-arm vibration exposure in compliance with of the international standard BS EN ISO 5349-1:2001. In particular, there has been limited attention to measurement of the appropriate frequency range and the application of the appropriate weighting filters within the previous work.…”
Section: Introductionmentioning
confidence: 99%
“…They provide transportation to many areas in the form of recreation, general fitness, military, courier services and bicycle racing. The first chain-driven model was developed around 1885 on the basic shape of the typical upright or safety bicycle [2][3][4][5]. This type of bicycle became very popular in the late 1880s as an alternative to the penny-farthing and now it is the most common type of bicycle.…”
Section: Introductionmentioning
confidence: 99%
“…[1]. An experimental study shows that larger tyre sizes and lower tyre inflation pressure, reduces the impact of track unevenness [2]. Another study shows that an optimum stiffness of front suspension fork can suggestively reduce vibration transmission to the rider [3].…”
Section: Introductionmentioning
confidence: 99%